Propagation of Dianthus deltoides L. by shoot culture - Popović Marija; Grbić Mihailo; Marković Marija (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2008)
The possibility of improving D. deltoides micropropagation was studied in the aim of reducing the number of vitrified and necrotic shoots. Micropropagation was performed on the medium with MS mineral solution, supplemented with 3% sucrose, 0.8% agar, 50 mg·L-1 mio-inositol, 0.025 mg·L-1 thiamin, 0.125 mg·L-1 nicotinic acid and 0.5 mg·L-1 glycine. The shoot multiplication was induced on 6-benzylaminopurine (BAP) and α-naphthalene acetic acid (NAA). Vitrification was successfully reduced, and the best results were achieved on the medium with 1 mg·L-1 BAP and 0.1 mg·L-1 NAA. Rooting was successful on the medium without hormones, and the acclimatisation percentage accounted for 92%.